A starch-based, crosslinked blend film with seawater-specific dissolution characteristics. (1st January 2023) - Jia, Yuxiang; Hsu, Yu-I; Uyama, Hiroshi
Abstract: Existing biodegradable plastics may not be ideal replacements of petroleum-based single-use plastics owing to their slow biodegradation in seawater. To address this issue, a starch-based blend film with different disintegration/dissolution speeds in freshwater and seawater was prepared. Poly(acrylic acid) segments were grafted onto starch; a clear and homogenous film was prepared by blending the grafted starch with poly(vinyl pyrrolidone) (PVP) by solution casting. After drying, the grafted starch was crosslinked with PVP by hydrogen bonds, owing to which the water stability of the film is higher than that of unmodified starch films in fresh water. In seawater, the film dissolves quickly as a result of disruption of the hydrogen bond crosslinks. This technique balances degradability in marine environment and water resistance in everyday environment, provides an alternative route to mitigate marine plastic pollution and could be potentially useful for single-use applications in different fields such as packaging, healthcare, and agriculture.